Struktura rzeczownikowych derywatów paradygmatycznych pochodnych od wyrażeń przyimkowych - Tomaszewska, Sławomira (Acta Universitatis Lodziensis. Folia Linguistica, 1992)
This article presents in detail the process of derivation as a result of which prepositional phrases are transformed into nouns. Special emphasis is laid on the relations between the nominal part of word-formation base and a derivative. In connection with this, two main groups of derivatives are distinguished. The first one comprises such words as e.g. bezrobocie, dorzecze, przedwiośnie, poddasze, podgardle, ubocze whose creation involves a change of the basic noun’s paradigm. The second group includes words such as bezsens, poplon, przedświt, przedpołudnie, zagranica in which the basic noun’s pattern of declension is not changed. In its derivative the basic noun has nominative form irrespective of its syntactic relationship to the preposition with which it was connected in the prepositional phrase.